THE EFFECT OF TAXPAYER INCOME, TAXATION SOCIALIZATION, TAXATION SANCTIONS AND AWARENESS OF TAXPAYER OBJECTIVES TO THE COMPLIANCE OF EARTH AND BUILDING TAXATION IN WONOREJO VILLAGE, PAGERWOJO DISTRICT - Yuni Kristanti (State Islamic Institute (IAIN) Tulungagung, 2020)
This study aims to examine the effect of taxpayer income, tax socialization, tax sanctions and awareness of taxpayers on compliance of land and building taxpayers in Wonorejo Village Pagerwojo District Tulungagung Regency partially and simultaneously. This research approach use a quantitative with primary data and secondary data. Data qollection in this study using a questionnaire and documentation . Sampling using a purposive sampling technique with a total sample of 100 respondents. Measurement in this study uses a Likert scale. The data analysis method used is multiple linear regression analysis. The results showed that taxpayer income, tax dissemination and tax sanctions partially had a positive but not significant effect on taxpayer compliance, awareness of taxpayers partially had a significant positive effect on taxpayer compliance. Income taxpayers, taxation socialization, tax sanctions and awareness of taxpayers simultaneously have a significant positive effect on the compliance of land and building taxpayers in Wonorejo Village, Pagerwojo District, Tulungagung Regency.